2021
DOI: 10.1016/j.jclinepi.2021.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Spin occurs in bariatric surgery randomized controlled trials with a statistically nonsignificant primary outcome: A systematic review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was reported that the authors added spin in the manuscripts requested by peer reviewers in 9% of the publications, and peer reviewers failed to identify spin in the abstract conclusions in 76% of the publications [Lazarus et al, 2016]. Several previously published methodological studies on spin in the abstracts of RCTs with statistically nonsignificant primary outcomes also reported a high prevalence of spin in various fields of medicine [Boutron et al, 2010;Arunachalam et al, 2017;Eleftheriadi et al, 2020;Wu et al, 2020;Guo et al, 2021;Rassy et al, 2021]. Among those previous studies, several studies assessed spin in dentistry.…”
Section: Interpretation Of the Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the authors added spin in the manuscripts requested by peer reviewers in 9% of the publications, and peer reviewers failed to identify spin in the abstract conclusions in 76% of the publications [Lazarus et al, 2016]. Several previously published methodological studies on spin in the abstracts of RCTs with statistically nonsignificant primary outcomes also reported a high prevalence of spin in various fields of medicine [Boutron et al, 2010;Arunachalam et al, 2017;Eleftheriadi et al, 2020;Wu et al, 2020;Guo et al, 2021;Rassy et al, 2021]. Among those previous studies, several studies assessed spin in dentistry.…”
Section: Interpretation Of the Main Findingsmentioning
confidence: 99%
“…Several methodological studies have assessed spin in the titles and abstracts of RCTs in medicine, including dentistry [Boutron et al, 2010;Lockyer et al, 2013;Arunachalam et al, 2017;Khan et al, 2019;Eleftheriadi et al, 2020;Wu et al, 2020;Guo et al, 2021;Ito et al, 2021;Rassy et al, 2021]. The prevalence of spin in those reviews was high, ranging from 34% to 70%.…”
Section: Introductionmentioning
confidence: 99%
“…And finally, recent reports indicate a high percentage (ranging from 47% to 66%) of detected spin across medical disciplines [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%